(untitled) - Cobbold, Richard S. C. (New York, 1970)
The content is essentially divided into four parts: an introductory survey; fabrication; theory of junction-gate and metal-insulator semiconducto transistors; and circuit applications.
Keywords: Transistor hiệu ứng trường,Field-effect transistors